Constraining the composition and quantity of organic matter used by abundant marine Thaumarchaeota - Alma E. Parada; Xavier Mayali; Peter K. Weber; Jessica Wollard; Alyson E. Santoro; Jed A. Fuhrman; Jennifer Pett‐Ridge; Anne E. Dekas (Environmental Microbiology, 2023)
Marine Group I (MGI) Thaumarchaeota were originally described as chemoautotrophic nitrifiers, but molecular and isotopic evidence suggests heterotrophic and/or mixotrophic capabilities. Here, we investigated the quantity and composition of organic matter assimilated by individual, uncultured MGI cells from the Pacific Ocean to constrain their potential for mixotrophy and heterotrophy. We observed that most MGI cells did not assimilate carbon from any organic substrate provided (glucose, pyruvate, oxaloacetate, protein, urea, and amino acids). The minority of MGI cells that did assimilate it did so exclusively from nitrogenous substrates (urea, 15% of MGI and amino acids, 36% of MGI), and only as an auxiliary carbon source (